Equity of Financial Protection Under National Health Insurance: A Concentration Index Analysis in East Nusa Tenggara - Muhammad Aslam Muwaffiq; Gilang Ramadhan; Antokalina Sari Verdiana; Dina Anjayani (Journal of Social Research, 2026)
This study addresses the challenge of financial protection under Universal Health Coverage (UHC), particularly in the context of Indonesia’s National Health Insurance (JKN) program. Although JKN has expanded access to healthcare services, evidence indicates that insurance coverage does not always prevent households from experiencing Catastrophic Health Expenditure (CHE), especially in geographically disadvantaged regions such as East Nusa Tenggara (NTT). Therefore, this research aims to evaluate the equity of financial protection by examining the incidence and socioeconomic distribution of CHE among households in NTT. This study employed a quantitative approach using secondary microdata from the 2025 National Socio-Economic Survey (SUSENAS), covering 13,063 households. CHE is defined as out-of-pocket health expenditure exceeding 40% of non-food expenditure. Households are ranked using an asset-based Wealth Index, and inequality is analyzed using the Concentration Index (CI) and Concentration Curve. The results show that 16.89% of households experienced CHE, indicating substantial financial vulnerability. The findings reveal a dual inequity pattern: CHE is concentrated among the poorest households for subsidized beneficiaries (negative CI), while among non-subsidized participants, it is concentrated among the wealthiest (positive CI), reflecting different spending behaviours. In conclusion, JKN has not fully achieved equitable financial protection. Policy interventions should address both access-related costs for the poor and service quality gaps to improve system effectiveness